Sistem Informasi Monitoring Proyek Berbasis Web Pada Desa Somagede Kabupaten Banyumas - Ragil Wijianto; Wijianto, Ragil; Diki, Dimas Diki; Maryani, Ina (Informatics and Computer Engineering Journal, 2021)
In this era of globalization, the development of information technology is moving very fast. As for computers, which are equipment created to facilitate human work and also the internet which is used as a means to obtain information easily. Somagede Village, Banyumas Regency has several ongoing projects, but some residents do not know this information because there is no available information system. Judging from these problems, the author makes a Scientific Work on a web-based project monitoring information system to overcome these problems. The making of this system uses data collection methods by observing projects in Somagede Village, interviewing the Somagede Village Head as a resource person. Through this system, it can be used as a monitoring medium for ongoing projects by community members.